Stakeholder Forum of the Sub-sector Working Group on Irrigation. 20 March 2024, Vientiane, Laos PDR - Inphonephong, Souphalack; Dubois, Mark (CGIAR, 2024)
Water management is still key in the setting where water resources are abundant, like Laos.